Tantangan dan Solusi dalam Implementasi Kompetensi Pedagogik di Sekolah Menengah Atas - Anggraini, Tiara; Irma, Ade; Revita, Rena (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
This study aims to examine the challenges and solutions in the implementation of pedagogical competence by a teacher in one of the high schools. The research was conducted with a descriptive qualitative approach through in-depth interviews and observation of teaching practices in the classroom. The focus of the study includes how teachers adjust learning methods to students' learning styles, build a conducive classroom atmosphere, manage time, and respond to student motivation and learning outcomes. The results show that teachers face obstacles in fostering enthusiasm for learning and adjusting learning strategies to the needs of diverse students. Nevertheless, teachers are able to develop creative and reflective approaches to overcome these obstacles, such as variations in teaching methods and material adjustments. The novelty of this study lies in the in-depth analysis of one teacher's practice as a representation of real challenges in the classroom. The findings are expected to provide practical insights for the development of teachers' pedagogical competence in the secondary school context.